Training need assessment: a must for developing an effective training programme for paraprofessionals, with special reference to the Library, University of Colombo - Adhikari, H.I.S.M. (University of Colombo, 2021)
Training Need Assessment (TNA) is an important approach in human resource development in finding the gap between the “Training” and “Needs of Training.” Although the training is very important in libraries, it was observed that most of the library staff in the University of Colombo have only training opportunities in Information Technology skills. Therefore, the present study aims to explore the training needs of the staff at the Library, University of Colombo with specific objectives of exploring staff training programmes available, determining the satisfaction level of prevailing staff training programs, and identifying specific problems areas in the training needs. Survey research was conducted by administrating questionnaires to forty paraprofessionals as census. The response rate was 90.36%. It was identified that training programmes on basic computer skills (Word processing, PowerPoint, and Excel) were available in the library and 97.22% were satisfied with those sessions. However, the respondents were not satisfied with the availability of training programmes and expected more opportunities to improve their skills. 91.66% have suggested new themes in Customer Care, Communication Skills, and Future Career Development, while 72.22% suggested Teamwork, Motivation, and leadership for training, and 69.44% requested training on ‘Online work’. Further, 95% preferred trainers to be external experts, while 72.22% preferred internal resource persons. All the respondents requested trainings through biannual workshops. 83.33% mentioned that the lack of training programmes hinders their training opportunities. All the respondents requested training for their career development. Thus, the study concluded that there is an urgent requirement for staff training at the library, University of Colombo. The present study recommends appointing a Training and Development Officer; developing training policies; periodically evaluating the training needs; design, develop and execute training programmes; and monitoring capacity building.
Keywords: Training; Need assessment; Library University of Colombo; Staff training